Three-dimensional numerical investigation of laminar flow in blind-tee pipes. (1st December 2020) - Han, Fenghui; Ong, Muk Chen; Xing, Yihan; Li, Wenhua
Abstract: Blind-tee pipes are often employed in process piping systems used in offshore and subsea oil and gas industry. The objective of the present study is to investigate the effects of blind-tee length, end-structure shape and flow velocity on the mixing condition inside blind-tee pipes. Three-dimensional numerical simulations are performed for the laminar flows in the pipes with blind-tee length varying from 1 D to 5 D at Re = 500, 1000, 1500 and 2000. Spherical and flat end-structure shapes are also investigated for the blind-tee section. Firstly, flow simulations in a straight pipe are performed, and the numerical results are compared with the analytical solutions. Then, the computed velocity profiles are used as the inlet velocity for the simulations of blind-tee pipes. Flow characteristics both inside and downstream the blind-tee section are numerically studied by analyzing the streamlines, pressure contours and velocity profiles. The results reveal that a higher inlet velocity and a blind-tee length no more than 3 D can achieve a better mixing condition for the fluid flow in blind-tee pipes; while stagnant flows are more prone to occur towards the end of the blind-tee section at low velocities with the length longer than 3 D, leading to potential fluid deposition in blind-tee pipes. Highlights: Laminar flow can form 1 to 3 flow circulations in the blind-tee section with blind-tee length B T L ≤ 5 D . With an increase in BTL or a decrease in Reynolds number, more flow circulations are generated with lower velocity and therefore increases the possibility of stagnant flow at the blind-tee end. The maximum size of the first circulation created by laminar flow in the blind tee is around 3D. A higher flow velocity and B T L ≤ 3 D can achieve a better mixing condition in blind-tee pipes.